2020
DOI: 10.3390/ijms21145081
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR-145-5p Causes Ceruloplasmin Interference with PHD-Iron Axis and HIF-2α Stabilization in Lung Adenocarcinoma-Mediated Angiogenesis

Abstract: For decades, lung cancer has been the leading cause of cancer-related death worldwide. Hypoxia-inducible factors (HIFs) play critical roles in mediating lung cancer development and metastasis. The present study aims to clarify how HIF’s over-activation affects lung cancer angiogenesis not only in a normoxic condition, but also a hypoxic niche. Our study shows that human lung cancer exhibits elevated levels of ceruloplasmin (CP), which has a negative impact on the prognosis of patients. CP affects the cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…[35][36][37] Zhou et al revealed that miR-145-5p suppressed the proliferation, migration and invasion of gastric cancer epithelial cells via the ANGPT2/NOD_LIKE_RECEPTOR axis. 39 Additionally, the loss of miR-145-5p caused ceruloplasmin interference with the PHD-Iron axis and HIF-2α stabilization in lung adenocarcinoma-mediated angiogenesis. 40 In CHOL cells, Zeng et al clarified that lncRNA TUG1 sponged miR-145-5p to promote intrahepatic CAA progression and regulate glutamine metabolism via the sirt3/GDH axis.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Zhou et al revealed that miR-145-5p suppressed the proliferation, migration and invasion of gastric cancer epithelial cells via the ANGPT2/NOD_LIKE_RECEPTOR axis. 39 Additionally, the loss of miR-145-5p caused ceruloplasmin interference with the PHD-Iron axis and HIF-2α stabilization in lung adenocarcinoma-mediated angiogenesis. 40 In CHOL cells, Zeng et al clarified that lncRNA TUG1 sponged miR-145-5p to promote intrahepatic CAA progression and regulate glutamine metabolism via the sirt3/GDH axis.…”
Section: Discussionmentioning
confidence: 99%
“…SARI knockout enhanced angiogenesis by regulating the expression of HIF-1α, VEGF and ceruloplasmin in mice [ 38 ]. In lung cancer cells, silencing ceruloplasmin enhanced the iron concentration and upregulated the activity of PHD1/2 to induce the hydroxylation of HIF-2 [ 39 ]. These results suggest that ceruloplasmin regulates HIF-2α activity through an iron/PHD cascade-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that ceruloplasmin regulates HIF-2α activity through an iron/PHD cascade-dependent pathway. Additionally, miR-145-5p directly targets ceruloplasmin expression, and increased ceruloplasmin contributes to activation of the PHD/HIF-2α/VEGF-A axis to facilitate cancer growth and metastasis in LUAD [ 39 ]. In addition to HIF-related pathways, other signaling pathways have been reported to mediate the dysregulation of ceruloplasmin.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-145-5p can directly target ceruloplasmin (CP), and loss of miR-145-5p in LUAD induces overexpression of CP. Overexpression of CP decreases Fe 2+ and prolyl hydroxylase domain (PHD) 1/2 levels while inhibiting HIF-2α, leading to the activation of tumor angiogenesis [ 42 ]. The expression of miR-320b is down-regulated and related to improved overall survival in patients with lung cancer.…”
Section: Angiogenesis Related Ncrnas In Lung Cancer Cellsmentioning
confidence: 99%